Otological Surgery of Acoustic Neuroma - XIA Yin; WANG Pu (Xiehe Yixue Zazhi, 2021)
Acoustic neuroma is the most common benign tumor in the internal auditory canal and cerebellopontine region.Its common clinical symptoms include unilateral sensorineural hearing loss, tinnitus and so on.Surgical resection is the predominant treatment of acoustic neuroma. The common approaches dominated by otologists include translabyrinthine approach, enlarged translabyrinthine approach, transotic approach, modified transotic approach, and middle cranial fossa approach; the approach dominated by neurosurgeons is retrosigmoid (suboccipital) approach. For small tumors with intact hearing, it is recommended to choose the middle cranial fossa approach. Those with large tumors who wish to preserve their hearing can adopt the suboccipital retrosigmoid approach; those who do not consider retaining hearing and have medium or small acoustic neuromas can adopt the translabyrinthe approach or through the transotic approach. With the development of microsurgical technology and the wide application of intraoperative nerve monitoring equipment, the retention rate of facial/cochlear nerve function for surgery of small and medium-sized acoustic neuroma has been significantly improved. In the future, more patients with acoustic neuroma are expected to be completely cured on the basis of preserving facial/cochlear nerve function.